Analisis Kedisiplinan Dan Kompensasi Terhadap Kinerja Aparatur Sipil Negara - Peni Wulandari; Arisyahidin Arisyahidin (Universitas Islam Kadiri, 2020)
The Nganjuk District Agricultural Office requires reliable human resources to achieve the stated goals. After understanding the importance of human resources as the activator of the organization, the organization must be able to manage, utilize and empower in such a way that the strengths of human resources in the organization can be optimized. For this reason, Employee Performance is emphasized. The objectives of this research are: (1).To determine the effect of discipline on employee performance; (2). To determine the effect of compensation on employee performance; (3) To find out the effect of discipline and compensation together on employee performance. The subjects of this study were employees of the Nganjuk District Agriculture Office with 75 employees. This study uses a quantitative approach. The research data were obtained by using questionnaire, observation and documentation techniques. The analysis technique used is multiple linear regression with t test and F test to test the research hypothesis. The results showed that, the correlation of discipline and compensation showed a positive and significant effect on the performance of Nganjuk District Agricultural Service employees both separately and simultancously, Effective contribution of discipline and compensation of 48,1% to employee performance.